PERSEPSI RECRUITER TERHADAP KOMPETENSI BAHASA INGGRIS DALAM PROSES RECRUITMENT CREW KAPAL DI PT TOS INDONESIA - Afza Syahzanani; Muhammad Dahri; Prima Yudha; Rizki Aini Rakhman (UNIMAR AMNI Semarang, 2026)
The international shipping industry demands high communication standards as seafarers come from diverse cultural and linguistic backgrounds. English has been established as the international working language through the Standard Marine Communication Phrases (SMCP) issued by the International Maritime Organization (IMO, 2002). Although English language competence has become part of the crew selection process at manning agencies, studies specifically examining how recruiters perceive this competence within the selection process remain considerably limited. This study aims to analyze the perceptions of recruiters at PT TOS Indonesia toward English language competence as a determining factor in the ship crew recruitment process. A qualitative descriptive approach was employed, with data collected through semi-structured interviews, direct observation, and company documentation. Data analysis was conducted using the interactive model of Miles and Huberman. The findings reveal that recruiters perceive English language competence as the principal determinant in crew selection, rather than a mere administrative requirement. Assessments were conducted situationally through four core indicators: the ability to comprehend work instructions in English, oral communication skills (speaking), proficiency in maritime terminology (Maritime English), and the ability to articulate operational reports contextually. Data showed that only 45.85% of 868 applicants passed the English selection stage. A 1–4 scoring rubric was applied to maintain objectivity, affirming that English language competence is an integral component of occupational safety within international maritime operations.